2013
DOI: 10.1007/s11427-012-4404-x
|View full text |Cite
|
Sign up to set email alerts
|

In vivo skin penetration and metabolic path of quantum dots

Abstract: The skin is the largest organ of the body and is a potential route of exposure to sunscreens and cosmetics containing nanoparticles; however, the permeability of the skin to these nanoparticles is currently unknown. In this paper, we studied the transdermal delivery capacity through mouse skin of water-soluble CdSeS quantum dots (QDs) and the deposition of these QDs in the body. QD solution was coated onto the dorsal hairless skin of male ICR mice. Fluorescence microscopy and transmission electron microscopy (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 22 publications
0
16
0
2
Order By: Relevance
“…Additionally, the metabolic rate of NPs in various organs is different. For example, while the accumulation of QDs in the liver and kidney could not be effectively eliminated, QDs in the spleen get eliminated within 24 h (Tang, Zhang, Song, Jin, & Xu, ).…”
Section: Absorption Distribution Metabolism and Excretion (Adme) Omentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the metabolic rate of NPs in various organs is different. For example, while the accumulation of QDs in the liver and kidney could not be effectively eliminated, QDs in the spleen get eliminated within 24 h (Tang, Zhang, Song, Jin, & Xu, ).…”
Section: Absorption Distribution Metabolism and Excretion (Adme) Omentioning
confidence: 99%
“…A reduced thickness of the epidermis and papillary layer with regular collagen fibers and inflammation, as well as the increased number of Langerhans cells and round cells were observed in the skin samples of animals treated with silver NPs (Korani et al, ). Researchers speculated that the main permeation mechanism of NPs into the intercellular spaces of the outermost stratum corneum layers in the skin of mice was via hydrophilic pathways, such as hair follicles, sweat pores, and the intercellular spaces between the corneocytes and other nanopores, made possible by the hydrophilic properties of several NPs (Tang et al, ). Although skin could be damaged by dermal exposure to NPs, the NPs ability to impair internal organs through penetrated NPs from the skin is extremely limited.…”
Section: The Impacts Of Nps On Major Target Organsmentioning
confidence: 99%
“…Tang et al [32] provided information on QDs penetration and distribution in skin and toxicity in organs. They studied the transdermal delivery capacity through mouse skin of water-soluble CdSeS QDs and the deposition of these QDs in the body.…”
Section: Penetration Of Quantum Dotsmentioning
confidence: 99%
“…Skin exposure to nanoparticles as pollution, antibacterials, and sun screen each have some toxicity concerns(115-117). Nanoparticle uptake measurements using quantum dots showed that penetration into the dermal layer is limited to the uppermost stratum corneum layers and the hair follicles(118). Those nanoparticles that enter the blood stream accumulate in the liver and kidney with poor clearance rates(118).…”
Section: Toxicity: Delivery Modes Mechanisms and Managementmentioning
confidence: 99%
“…Nanoparticle uptake measurements using quantum dots showed that penetration into the dermal layer is limited to the uppermost stratum corneum layers and the hair follicles(118). Those nanoparticles that enter the blood stream accumulate in the liver and kidney with poor clearance rates(118). Toxicity can directly affect skin cells by forming reactive oxygen species along with autophagic vacuole accumulation and mitochondria damage(119).…”
Section: Toxicity: Delivery Modes Mechanisms and Managementmentioning
confidence: 99%